Empreendimentos e perfil dos empreendedores do município de Vila Flor - RN - Di Gouveia, Kelly Gonçalves (Universidade Federal Rural do Semi-Árido, 2019)
The present study aimed to identify and characterize the entrepreneurs of the city of Vila Flor, the city located in the south coast microregion of the state of Rio Grande do Norte. The quiet city was one of the first nuclei of Portuguese colonization of the state. The phenomenon of entrepreneurship has been growing more and more over the years, being one of the main factors of economic, social and technological changes in the world. The importance of understanding entrepreneurial activity, as well as the profile of the entrepreneur, is of paramount importance for the development of society. In this sense, for the construction and development of this work, it was used as methodology a bibliographic-documentary research, through the classic literature, a field research, besides the case study. Thus, a form was applied, which sought to analyze the distribution by gender, age, education level of entrepreneurs, as well as the distribution of their enterprises by branch, size, age and their distribution according to economic sectors. As well as the use of commercially available information technologies. Results were soon found that allow us to draw a profile of entrepreneurs in the municipality.
Monografia
Keywords: Empreendedor; Novas tecnologias; Empreendedorismo; Entrepreneur; New technologies; Entrepreneurship; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA